Open concert. Analysis of the existing variables in the construction process of a lyric singing degree recital (2020)
The main object of the following article is to methodologically narrate the process through which my recital degree was constructed starting with the question: how does one make a lyrical singing recital degree inviting and interesting for the audience? The question arose mainly because my interest resided in keeping the inexperienced audience's attention during the whole concert. In order to accomplish this, I began with the analysis of previous recitals, obtaining a series of structural elements that were later altered in search of creating a coherent and integral staging capable of maintaining the audience's attention and whose results could be quantitatively and qualitatively analyzed.